2003
DOI: 10.1034/j.1600-051x.2003.00157.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic risk factors for periodontal attachment loss among adults in the United States

Abstract: These results support earlier findings regarding the central role of cigarette smoking in the etiology of periodontal loss of attachment, a role due in large part to the substantial relationship between smoking and severe periodontal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
148
2
13

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(178 citation statements)
references
References 26 publications
(31 reference statements)
14
148
2
13
Order By: Relevance
“…While these have had methodological differences, they have consistently shown that smoking is a primary risk factor. The findings from NHANES III have shown that cigarette smoking, caries rate, and gender are independently associated with clinical attachment loss in 20-49-year-olds (Hyman & Reid 2003). Similar findings with respect to gender and smoking as risk factors for periodontal attachment loss have also been reported elsewhere (Beck et al 1990;Norderyd & Hugoson 1998, Ogawa et al 2002, Paulander et al 2004), but have not always confirmed the association of gender with periodontal attachment loss (Norderyd & Hugoson 1998).…”
supporting
confidence: 63%
“…While these have had methodological differences, they have consistently shown that smoking is a primary risk factor. The findings from NHANES III have shown that cigarette smoking, caries rate, and gender are independently associated with clinical attachment loss in 20-49-year-olds (Hyman & Reid 2003). Similar findings with respect to gender and smoking as risk factors for periodontal attachment loss have also been reported elsewhere (Beck et al 1990;Norderyd & Hugoson 1998, Ogawa et al 2002, Paulander et al 2004), but have not always confirmed the association of gender with periodontal attachment loss (Norderyd & Hugoson 1998).…”
supporting
confidence: 63%
“…Smoking has been associated with indicators of severe periodontal disease such as periodontal loss of attachment, bone loss and premature tooth loss in cross-sectional [45][46][47][48][49][50][51][52] and longitudinal studies [53][54][55][56], and the outcome of periodontal treatment has been shown to be less favourable or indeed unfavourable in smokers compared with nonsmokers [57,58]. Several studies have also explored the relation between exposure level and disease severity and found a correlation between increasing exposure to smoking and severe periodontal disease [47,53,56,59].…”
Section: Periodontitismentioning
confidence: 99%
“…Periodontal diseases are a group of infectious diseases affecting the O Minaya -Chronic periodontitis periodontitis has been considered to be more common in people aged more than 30, having inadequate oral hygiene (10,11) and/or high levels of stress (12). Its distribution is also associated with smoking (13,14) and low socioeconomic status (LSS) (15). In addition to these socio-demographic, socioeconomic, and behavioral factors, other factors have been mentioned in association with chronic periodontitis (3,10,(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%